Redefining Manhood and Womanhood: Insights from the Oldest Indonesian Muslim Women Organization, 'Aisyiyah - Syamsiyatun, Siti (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2022)
This paper asks the question: why is it mostly men who define good manhood and womanhood? Where are women’s voices on these contested concepts? To elucidate women’s conceptualization of manhood and womanhood, this study draws on the oldest Indonesian Muslim women organization in Indonesia, ‘Aisyiyah, by examining its published treatises Interviews with 'Aisyiyah activists were also taken in June and August 2021 to enrich and clarify data from these documents. Amongst the most significant findings are that ‘Aisyiyah has argued for a very different kind of manhood and womanhood from those promoted by conservative groups, religiously and culturally. ‘Aisyiyah does jihad for a mutual and reciprocal idea of good manhood and womanhood; that means good men must behave well to women, and good women must respect men. Their arguments are based on contextual interpretations of Qur’anic texts and Prophetic traditions as well as local and cultural notions of proper manhood and womanhood.